Obstruction of justice in Criminal Law: A Juridical Review of Obstruction of Law Enforcement by Law Enforcement Officers - Edi Yunara (PT. Anagata Sembagi Education, 2024)
Criminal law enforcement in Indonesia is not only faced with technical and structural obstacles, but also with serious threats from within the system itself, especially through the practice of obstruction of justice carried out by law enforcement officials. Actions such as destruction of evidence, intimidation of witnesses, manipulation of information, and interference with the investigation process have been proven to occur in a number of major cases, one of which is in the case of the murder of Brigadier J. The purpose of this study is to juridically analyze the concept of obstruction of justice, evaluate its regulation in Indonesia's positive criminal law, and examine the criminal liability of law enforcement officials involved in act. This research uses normative legal research methods with a legislative approach, and is analyzed qualitatively descriptively through literature studies and case studies. The results of the study show that although the term obstruction of justice has not been explicitly regulated in the Criminal Code, the substance of the act has been reflected in various general and special criminal provisions such as Articles 221, 231, 233 of the Criminal Code and Article 21 of the Corruption Law. However, scattered and multi-interpreted arrangements lead to weak law enforcement effectiveness against perpetrators, especially if they come from law enforcement institutions.